Energy Consumption of Hash Functions - Damasevicius, R.; Ziberkas, G.; Stuikys, V.; Toldinas, J. (Elektronika ir Elektrotechnika, 2012)
We analyse energy efficiency versus quality characteristics of hashing algorithms in a mobile device and describe methodologies for energy measurement on a Java-enabled smart phone. Energy efficiency of 17 hash functions (Adler32, Crc16, Crc32, Haval256, MD2, MD4, MD5, MD6, SHA1, SHA224, SHA256, SHA384, SHA512, Skein, SV1, Tiger, Whirlpool) is evaluated using the GSM modem-based battery charge measurement method, and quality is evaluated using the Avalanche and Chi-square tests. The results show that the most energy-efficient hash function on a mobile device is SV1 for cryptographic applications, and crc16 for non-cryptographic applications. DOI: http://dx.doi.org/10.5755/j01.eee.18.10.3069